Magma Supply System at Batur Volcano Inferred from Volcano-Tectonic Earthquakes and Their Focal Mechanism - Hidayati, Sri; Sulaeman, C. (Geological Agency, 2013)
DOI:Â 10.17014/ijog.v8i2.159The Volcano-Tectonic (VT) earthquakes occurring during September - November 2009 were analyzed. The result shows that the epicentres aligning in NE- SW direction coincided with the weak zone of Batur Volcano Complex. The focal zone is located at the depth around 1.5 - 5.5 km beneath the summit. Migration of magma was detected by ground deformation measured by GPS and focal mechanism. Mechanism of VT earthquake shows mostly normal fault types during the swarm in November 2009.